Can socialized services reduce agricultural carbon emissions in the context of appropriate scale land management? - Chen, Zhongwei; Tang, Can; Liu, Bo; Liu, Pei; Zhang, Xueyan (Frontiers in Environmental Science, 2022)
In order to achieve low carbon transformation and green development in agriculture, we analyzed the effects of different types of socialized services on agricultural carbon emissions based on provincial panel data from 2010 to 2020 in China. We further analyzed the possible ways for agricultural social services to reduce the intensity of agricultural carbon emissions with the help of mediating effect model. The results show that socialized services can provide basic services, production and operation services, financial services, and circulation services for the agricultural production chain, which can significantly reduce the agricultural carbon emissions intensity. The results of the intermediation effect suggest that socialized services can break the labor constraint by promoting the scale effect, and thus reduce the agricultural carbon emissions intensity. However, the mediation effect of technology diffusion is not significant. The reason is that although the diffusion of agricultural technology can improve the efficiency of resource utilization, the diffusion of technology also leads to the use of elements such as high concentrations of chemicals and heavy agricultural tools which may increase carbon emissions. In addition, the effect of socialized services on reducing agricultural carbon emissions intensity shows obvious spatial heterogeneity, with the reduction gradually increasing from coastal to inland provinces and from eastern to western regions.